Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Complex interplay between the microalgae and their microbiome in production raceways - Judith Traver-Azuara; Caterina R. Giner; Carmen García-Comas; Ana Sánchez-Zurano; Martina Ciardi; Gabriel Acién; Sofiya Bondarenko; Aleix Obiol; Ramon Massana; Maria Montserrat Sala; Ramiro Logares; Pedro Cermeño (Bioresource Technology, 2025)

GLOSSAQUA : A global dataset of size spectra across aquatic ecosystems - Zeynep Ersoy; Charlotte Evangelista; Aitor Larrañaga; Daniel M. Perkins; Javier Sánchez‐Hernández; Teofana Chonova; David Cunillera‐Montcusí; Carmen García‐Comas; Jorge García‐Girón; Ioar de Guzman; Justin Pomeranz; Victor Saito; et al. (Ecology, 2025)
Body size is a key trait in ecology due to its influence on metabolism and many other life‐history traits that affect population and community responses to environmental variation as well as ecosystem properties. The size spectrum represents the relationship between abundance (or biomass) and body size, independent of species identity. Size spectrum parameters, such as the slope or intercept, have been applied extensively as indicators of ecological status across multiple ecosystem types. The GLOSSAQUA dataset includes data from mainly heterotrophic communities composed of single (e.g., zooplankton, macroinvertebrates, or fish) to multiple taxonomic groups (e.g., from primary consumers to apex predators, and phytoplankton to large zooplankton), across diverse spatial and temporal scales, from surveys in freshwater (43% studies), marine (52% studies) and brackish (5% studies) ecosystems. In total, we compiled a unique global dataset of 8459 size spectrum slopes or exponents, 5237 intercepts, and 4,497 linearity coefficients (i.e., defined by the R 2 of the linear fit of the size spectrum) from 127 articles and gray literature (i.e., unpublished datasets). The current dataset aims to help identify the main drivers shaping aquatic size spectrum parameters at a global scale and contribute to cross‐ecosystem comparisons. GLOSSAQUA can serve to explore questions such as factors influencing spatial and temporal dynamics of community size structure, comparing the response of community size structure between natural versus human‐impacted sites, and comparing global patterns in different aquatic ecosystems. We encourage researchers, especially those from underrepresented geographical areas (e.g., South Hemisphere and Asia) to fuel this dataset in the future. The dataset is provided under a CC‐BY‐NC‐S4 4.0 license, and users are encouraged to cite this data paper when using the data.

Unlocking energy potential: Decarbonizing water reclamation plants with salinity gradient energy recovery - T. Sampedro; L. Gómez-Coma; I. Ortiz; R. Ibañez (Science of The Total Environment, 2024)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

The removal of dissolved organic matter by marine sponges is a function of its composition and concentration: An in situ seasonal study of four Mediterranean species - M. Ribes; G. Yahel; C. Romera-Castillo; R. Mallenco; T.M. Morganti; R. Coma (Science of The Total Environment, 2023)

SWRO concentrates for more efficient wastewater reclamation - T. Sampedro; C. Tristán; L. Gómez-Coma; J. Rioyo; M. Sainz; I. Ortiz; R. Ibañez (Desalination, 2023)

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

Response of the seagrass Posidonia oceanica and its associated N 2 fixers to high business‐as‐usual climate change scenario in winter - Nona S. R. Agawin; Mª Guadalupe Gil Atorrasagasti; Aida Frank Comas; Víctor Fernández‐Juárez; Xabier López‐Alforja; Iris E. Hendriks (Limnology and Oceanography, 2021)
We investigated the effects of increasing seawater temperature and CO 2 concentration based on a high business‐as‐usual climate change scenario by year 2100 on the photosynthetic performance and productivity of Mediterranean seagrass Posidonia oceanica and alkaline phosphatase and N 2 ‐fixing activities of microbes associated with different plant parts during winter when the plants may be thermally more vulnerable. Our results suggest that elevated CO 2 and temperature benefit the overall photosynthetic performance of P. oceanica . Despite the benefits, the magnitude of respiration increased with elevated CO 2 resulting in a negative carbon balance for P. oceanica in winter. This trend is contradictory to the general notion of decreased respiration in plants with increasing CO 2 , and warrants future investigation on the mechanisms behind the opposite trend. Changes of alkaline phosphatase activities found here may not be a direct consequence of the different treatments, but indirectly, through changes in the demand for dissolved inorganic phosphorus for N 2 fixers. Of the several groups of N 2 fixers tested for nifH expression (a proxy for activity of nitrogenase, the enzyme required for N 2 fixation), only the unicellular N 2 ‐fixing cyanobacterial phylotypes, UCYNB and UCYNC, actively transcribed with a positive nifH transcription response of UCYNC to elevated CO 2 and temperature. Our results suggest that in future climate scenarios, the structure and diversity of N 2 microbial communities associated with seagrasses may change and high‐light the importance of investigating the responses of different groups individually in their natural habitat substrates.

Trophic niche separation that facilitates co‐existence of high and low microbial abundance sponges is revealed by in situ study of carbon and nitrogen fluxes - T. Morganti; R. Coma; G. Yahel; M. Ribes (Limnology and Oceanography, 2020)

Correction to: A 50-year sediment record of algal assemblage changes in Hanabanilla Reservoir, Cuba - Yeny Labaut; Pablo A. Macchi; Augusto A. Comas; Carmen R. Betancourt; Misael Díaz-Asencio (Journal of Paleolimnology, 2020)

A 50-year sediment record of algal assemblage changes in Hanabanilla Reservoir, Cuba - Yeny Labaut; Pablo A. Macchi; Augusto A. Comas; Carmen R. Betancourt; Misael Díaz-Asencio (Journal of Paleolimnology, 2020)

Lymnaeid Snail Vectors of Fascioliasis, Including the First Finding of Lymnaea neotropica in Ecuador, Assessed by Ribosomal DNA Sequencing in the Southern Zone Close to the Peru Border - A. F. Villavicencio; M. Dolores Bargues; Patricio Artigas; R. Guamán; S. M. Ulloa; J. Romero; David Osca; Santiago Mas-Coma (Acta Parasitologica, 2019)

Evidence for coral range expansion accompanied by reduced diversity of Symbiodinium genotypes - Carsten G. B. Grupstra; Rafel Coma; Marta Ribes; Karine Posbic Leydet; John Everett Parkinson; Kelly McDonald; Marc Catllà; Christian R. Voolstra; Michael E. Hellberg; Mary Alice Coffroth (Coral Reefs, 2017)

Trophic niche separation that facilitates co‐existence of high and low microbial abundance sponges is revealed by in situ study of carbon and nitrogen fluxes - T. Morganti; R. Coma; G. Yahel; M. Ribes (Limnology and Oceanography, 2017)
Sponges are commonly divided into high (HMA) and low (LMA) microbial‐abundance species according to the bacterial biomass in their tissue. These two groups reflect distinct aquiferous structures and feeding strategies. In the NW Mediterranean coralligenous community, HMA and LMA sponges are often packed in dense, multispecies assemblages that cover many pinnacles and overhangs. We investigated the metabolism of HMA and LMA species that cohabitate the coralligenous community by sampling in situ the inhaled and exhaled water. Sponges consumed plankton, dissolved organic carbon (DOC), and ammonium in relation to their abundance in ambient water. The plankton retention efficiency was high for all species. DOC was the main source of C for the sponge species, accounting for ∼ 90% of the examined sources. Nitrogen fluxes markedly differed between the two groups: plankton was the main source of nitrogen for LMAs that excreted dissolved organic nitrogen (DON) and ammonium. The nitrogenous waste products of LMAs were found to be the major source of nitrogen (up to 97%) for HMAs that efficiently removed DON and ammonium and excreted nitrate. The different capacity of both sponge strategies to use dissolved resources suggests a partial trophic niche separation related to HMA‐LMA dichotomy as a mechanism facilitating their dense co‐existence in the community. Our findings suggest that a mixed assemblage of sponges (and their associated microbes) is able to utilize the suspended particulate and dissolved material more efficiently than a single species population and may contribute to the understanding of the phenomena of the stability and diversity of dense sponge assemblages in oligotrophic habitats.

Neisseria gonorrhoeae antimicrobial susceptibility in Barcelona: penA, ponA, mtrR, and porB mutations and NG-MAST sequence types associated with decreased susceptibility to cephalosporins - J. Serra-Pladevall; M. J. Barberá; S. Rodriguez; R. Bartolomé-Comas; G. Roig; R. Juvé; A. Andreu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

No effects of Bacillus thuringiensis maize on nontarget organisms in the field in southern Europe: a meta-analysis of 26 arthropod taxa - C. Comas; B. Lumbierres; X. Pons; R. Albajes (Transgenic Research, 2014)

Specificity and temporal dynamics of complex bacteria–sponge symbiotic interactions - Johannes R. Björk; C. Díez-Vives; Rafel Coma; Marta Ribes; José M. Montoya (Ecology, 2013)
Microbes are known to form intricate and intimate relationships with most animal and plant taxa. Microbe–host symbiotic associations are poorly explored in comparison with other species interaction networks. The current paradigm on symbiosis research stems from species‐poor systems where pairwise and reciprocally specialized interactions between a single microbe and a single host that coevolve are the norm. These symbioses involving just a few species are fascinating in their own right, but more diverse and complex host‐associated microbial communities are increasingly found, with new emerging questions that require new paradigms and approaches. Here we adopt an intermediate complexity approach to study the specificity, phylogenetic community structure, and temporal variability of the subset of the most abundant bacteria associated with different sponge host species with diverse eco‐evolutionary characteristics. We do so by using a monthly resolved annual temporal series of host‐associated and free‐living bacteria. Bacteria are very abundant and diverse within marine sponges, and these symbiotic interactions are hypothesized to have a very ancient origin. We show that host–bacteria reciprocal specialization depends on the temporal scale and level of taxonomic aggregation considered. Sponge hosts with similar eco‐evolutionary characteristics (e.g., volume of tissue corresponding to microbes, water filtering rates, and microbial transmission type) have similar bacterial phylogenetic community structure when looking at interactions aggregated over time. In general, sponge hosts hypothesized to form more intricate relationships with bacteria show a remarkably persistent bacterial community over time. Other hosts, however, show a large turnover similar to that observed for free‐living bacterioplankton. Our study highlights the importance of exploring temporal variability in host–microbe interaction networks if we aim to determine how specific and persistent these poorly explored but extremely common interactions are.

Cancer chemotherapy reduces plasma total polyphenols and total antioxidants capacity in colorectal cancer patients - R. Santiago-Arteche; P. Muñiz; M. Cavia-Saiz; C. Garcia-Giron; M. García-Gonzalez; Beatriz Llorente-Ayala; M. J. Coma-del Corral (Molecular Biology Reports, 2012)

Functional convergence of microbes associated with temperate marine sponges - M. Ribes; E. Jiménez; G. Yahel; P. López‐Sendino; B. Diez; R. Massana; J. H. Sharp; R. Coma (Environmental Microbiology, 2012)
Summary Most marine sponges establish a persistent association with a wide array of phylogenetically and physiologically diverse microbes. To date, the role of these symbiotic microbial communities in the metabolism and nutrient cycles of the sponge‐microbe consortium remains largely unknown. We identified and quantified the microbial communities associated with three common Mediterranean sponge species, Dysidea avara , Agelas oroides and Chondrosia reniformis ( Demospongiae ) that cohabitate coralligenous community. For each sponge we quantified the uptake and release of dissolved organic carbon (DOC) and nitrogen (DON), inorganic nitrogen and phosphate. Low microbial abundance and no evidence for DOC uptake or nitrification were found for D. avara . In contrast A. oroides and C. reniformis showed high microbial abundance (30% and 70% of their tissue occupied by microbes respectively) and both species exhibited high nitrification and high DOC and NH 4 + uptake. Surprisingly, these unique metabolic pathways were mediated in each sponge species by a different, and host specific, microbial community. The functional convergence of microbial consortia found in these two sympatric sponge species, suggest that these metabolic processes may be of special relevance to the success of the holobiont.

From global to local genetic structuring in the red gorgonian Paramuricea clavata : the interplay between oceanographic conditions and limited larval dispersal - K. MOKHTAR‐JAMAÏ; M. PASCUAL; J.‐B. LEDOUX; R. COMA; J.‐P. FÉRAL; J. GARRABOU; D. AURELLE (Molecular Ecology, 2011)
Defining the scale of connectivity among marine populations and identifying the barriers to gene flow are tasks of fundamental importance for understanding the genetic structure of populations and for the design of marine reserves. Here, we investigated the population genetic structure at three spatial scales of the red gorgonian Paramuricea clavata (Cnidaria, Octocorallia), a key species dwelling in the coralligenous assemblages of the Mediterranean Sea. Colonies of P. clavata were collected from 39 locations across the Mediterranean Sea from Morocco to Turkey and analysed using microsatellite loci. Within three regions (Medes, Marseille and North Corsica), sampling was obtained from multiple locations and at different depths. Three different approaches (measures of genetic differentiation, Bayesian clustering and spatially explicit maximum‐difference algorithm) were used to determine the pattern of genetic structure. We identified genetic breaks in the spatial distribution of genetic diversity, which were concordant with oceanographic conditions in the Mediterranean Sea. We revealed a high level of genetic differentiation among populations and a pattern of isolation by distance across the studied area and within the three regions, underlining short effective larval dispersal in this species. We observed genetic differentiation among populations in the same locality dwelling at different depths, which may be explained by local oceanographic conditions and which may allow a process of local adaptation of the populations to their environment. We discuss the implications of our results for the conservation of the species, which is exposed to various threats.

Mass mortality in Northwestern Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2009)
Late in summer 2003, extensive mass mortality of at least 25 rocky benthic macro‐invertebrate species (mainly gorgonians and sponges) was observed in the entire Northwestern (NW) Mediterranean region, affecting several thousand kilometers of coastline. We were able to characterize the mortality event by studying six areas covering the main regions of the NW Mediterranean basin. The degree of impact on each study area was quantified at 49 sites by estimating the proportion of colonies affected in populations of several gorgonian species compared with reference data obtained in years without mortality signs. According to these data, the western areas (Catalan coast and Balearic Islands) were the least affected, while the central areas (Provence coast and Corsica‐Sardinia) showed a moderate impact. The northernmost and eastern areas (Gulf of Genoa and Gulf of Naples) displayed the highest impact, with almost 80% of gorgonian colonies affected. The heat wave of 2003 in Europe caused an anomalous warming of seawater, which reached the highest temperatures ever recorded in the studied regions, between 1 and 3 °C above the climatic values (mean and maximum). Because this exceptional warming was observed in the depth ranges most affected by the mortality, it seems likely that the 2003 anomalous temperature played a key role in the observed mortality event. A correlation analysis between temperature conditions and degree of impact seems to support this hypothesis. Under the present climate warming trend, new mass mortality events may occur in the near future, possibly driving a major biodiversity crisis in the Mediterranean Sea.

Mass mortality in NW Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2008)

Effects of a mass mortality event on gorgonian reproduction - C. Linares; R. Coma; M. Zabala (Coral Reefs, 2008)

Temporal variability in zooplankton prey capture rate of the passive suspension feeder Leptogorgia sarmentosa (Cnidaria: Octocorallia), a case study - S. Rossi; M. Ribes; R. Coma; J.-M. Gili (Marine Biology, 2004)

Different Kv2.1/Kv9.3 heteromer expression during brain and lung post-natal development in the rat - M. Coma; R. Vicente; I. Tsevi; M. Grande; M. M. Tamkun; A. Felipe (Journal of Physiology and Biochemistry, 2002)

Prey capture by a benthic coral reef hydrozoan - R. Coma; M. Ribes; C. Orejas; J.-M. Gili (Coral Reefs, 1999)

Horizontal Transfer of Matter by a Cave‐Dwelling Mysid - R. Coma; M. Carola; T. Riera; M. Zabala (Marine Ecology, 1997)
The role of a cave‐dwelling mysid population as a matter carrier was evaluated in a cave of the Medes Is. (NW Mediterranean) during 1988–89. Hemimysis spehmcola (L edoyer , 1963) is a gregarious mysid whose swarms migrate daily from the inner end of the cave ‐ where they remain during the day–to the exterior where they feed during the night. Fecal pellet composition, pellet egestion and pellet decomposition were measured in order to evaluate the transfer of matter by mysids. Based on the strong daily behavioural rhythms of these mysids. special importance was attached to the sampling frequency (every 2 h). In order to assess seasonal variability, four daily cycles were evaluated within a year. In situ incubations were carried out to determine changes on the egestion rates, morphology, weight and composition (AA. C: N ratios) of pellets in the course of a day. The number of pellets deposited inside the cave was estimated using containers distributed along the cave bottom by SCUBA divers. Fecal pellets showed an amorphous composition, whereby diatom frustules, dinoflagellate loricae and coccolithoporids were very scarce. About 25% of the body weight were estimated to be egested daily as fecal pellets, suggesting a detritivorous feeding habit. The population oscillated seasonally between 1 and 12 millions. Individuals egested between 1.6 and 3.5 pellets a day into the cave, each averaging from 9.4 to 11.9 μg DW, 0.5 to 1.0 μg C and 0.046 to 0.27 μg N. Therefore, the population carried daily about 20 407 g DW POM. 2–21 g C and 0.5 2.7 g N from outside to inside the cave. Pellets decomposed very quickly; between 20 to 50% of both C and N were released from pellets in less than 2 h after egestion. Oxidation of pellets theoretically consumes an amount of oxygen which agrees with the high BOD values previously reported for this cave. Marine caves are generally viewed as strictly oligotrophic systems; dense mysid populations, however, could strongly modify the trophic relationships in marine caves.